In vitro antioxidant activities of n-butanol extract of Helianthemum confertum - Radja Djebbari; Yasmine Chemam; Amel Amrani; Soumia Lassed; Nassima Boubekri Boubekri; Nassima Boubekri Boubekri; Djamila Zama; Fadila Benayache; Samir Benayache (International Journal of Phytomedicine, 2015)
Antioxidants play an important role to protect damage caused by oxidative stress. Plants having phenolic contents are reported to possess antioxidant properties. The basic aim of this research was to investigate the antioxidant properties of n-butanol extract of Helianthemum confertum, Cistaceae family. The antioxidant activities and phenolic contents of n-butanol extract were evaluated in vitro using spectrophotometer methods. There antioxidant activities were determined by DPPH (1,1-diphenyl-2-picrylhydrazine) radical scavenging assay and lipid peroxidation inhibition by TBARS method. Antioxidant activities were compared to ascorbic acid. Measurement of total phenolic compounds and total flavonoids content of the n-butanol extract of Helianthemum confertum were achieved using Folin-Ciocalteau reagent and AlCl3 respectively. The results showed that this extract containing 263.33±19.85µg of gallic acid equivalents/mg extract of total phenolic and 25.35±3.15µg of quercetin equivalents/mg extract total flavonoids.